Case Report: Ultrasound-Guided Percutaneous Microwave Ablation of Focal Nodular Hyperplasia in a 9-Year-Old Girl - Yao, Zhiguang; Zeng, Qingjing; Yu, Xuan; Lin, Shulian; Jiang, Shuanglan; Ma, Da; Li, Kai (Frontiers in Pediatrics, 2021)
Focal nodular hyperplasia (FNH) is a rare benign tumor-like space-occupying lesion of the liver, which is especially rare in children. Since there have been no reports of malignant progression of this disease and lesions remain unchanged for a long time or even disappear in some cases, whether clinical treatment is needed remains controversial. However, when the diagnosis is unclear, the patient has symptoms or the lesion grows during follow-up, clinical treatment should be considered. Here, we report the first case of FNH near the gallbladder treated by ultrasound-guided percutaneous microwave ablation (MWA) in a 9-year-old girl.